Genetic variability and bottleneck analysis of Barbari goat population using microsatellite markers - SHARMA, REKHA; KUMAR, DlNESH; PANDEY, A K; DIXIT, S P; AHLAWAT, S P S (The Indian Journal of Animal Sciences, 2011)
Genetic variation at 24 microsatellite loci and genetic bottleneck hypothesis were examined for Barbari goat population found in Uttar Pradesh, India. The estimates of genetic variability such as effective number of alleles and gene diversities revealed substantial genetic variation. Shannon’s information index as indicator of polymorphism across studied loci, and Nei’s expected heterozygosity were 1.183 and 0.58Â±O.191, respectively. The population was observed to be significantly differentiated into different groups, and showed heterozygote deficiency (f=O.202Â±O.044). The population has not sutfered bottleneck in recent past. The study revealed that the Barbari goat breed needs genetic management for its conservation and improvement. Â